The influence of customer participation and convenience on customer satisfaction: a multiple mediation - Souza, Álan Andrew de; Damacena, Cláudio; Araújo, Clécio Falcão; Carvalho, Bianca Pinto; Seibt, Nathália Gris (Revista de Administração da UFSM, 2023)
Purpose -The purpose of this paper is to present a model that connects predictors of customer satisfaction considering Service Domain-Logic assumption and convenience and quality of service as sources that were identified as relevant aspects for customer satisfaction related to financial services. Design/methodology/approach – Survey of a sample of six hundred and eight respondents was obtained. Structural equation modeling was used for data analysis to test research hypotheses. Findings - The predictive effects of convenience, economic value, and quality of service have proved to be significant for customer satisfaction. Perceived service quality was identified as a mediator of the relationship between convenience and customer satisfaction. Research limitations - This sample may have caused a few biases in the results, because it was selected by convenience. Practical implications - The findings have implications for organizations since they demonstrate that improving service value is a means of increasing customer satisfaction. To ensure that the customer finds the interaction with the banking service to be appealing and to offer valuable benefits, the banking service should therefore allow for customer participation to increase the perception of economic value and, more importantly, to facilitate the dissemination of information Originality/Value - This study brings results that show that customer participation impacts positively on the perception of economic value, but it is not the key for customer satisfaction in financial services. This result proves that the effects of customer participation are more complex than others before mentioned.